Motivações intrínsecas e extrínsecas na propensão à corrupção de agentes públicos - Carlos, Luiz Gustavo de Castro (2019)
This study approached the relationship between intrinsic (cognitive factors) and extrinsic (external environment) motivations and the process of corrupt decision making by civil servants. Specifically, it used the propensity to corruption, measured through the dimensions of moral disengagement and ethical organizational culture. This research is justified by the importance of deepening the studies regarding the motivations of agents to corruption and that may interfere in their choices. The collection of data took place through the application of questionnaires, in two public agencies of different spheres of action (municipal and federal), which were answered by 174 civil servants from July 2019 to September 2019 (102 federal servants and 72 municipal servants). The analysis of the variables was carried out quantitatively using the multiple linear regression method, using the SmartPLS® 3.0 software. The theoretical contribution focuses on identifying associations between intrinsic motivations and moral disengagement and between extrinsic motivations and organizational ethical culture. As a practical contribution, it is expected that the results may help managers who seek to reduce the propensity to corruption to identify the main deficiencies of their functional body, redesign their work processes, better manage the risks of deviant actions, identify places where there is a greater need for attention due to corrupt behavior, adequately select bosses and to implement prevention, training and control measures in work processes.